2015
DOI: 10.2141/jpsa.0140093
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive and Taste-related Compounds in Defatted Freeze-dried Chicken Soup Made from Two Different Chicken Breeds Obtained at Retail

Abstract: The aim of this study was to compare the bioactive and taste-related compounds in defatted freeze-dried chicken soup (DFDS) made from Korean native chickens (Woorimatdag TM , KNC) and commercial broilers (CB) available at retail. The betaine, carnitine, histidine dipeptide, creatine, nucleotide, free amino acid content, and fatty acid composition were analyzed in six DFDS samples from each breed. Histidine dipeptides were not detected in any DFDS samples. DFDS made with KNC had significantly higher betaine, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 47 publications
2
34
0
Order By: Relevance
“…[2,10,31] The decreases in IMP, GMP, and Hx could result from both their migration from the meat into the broth and the thermal degradation of IMP to inosine during stewing. [32] The decrease in the IMP in the chicken meat during stewing were consistent with results in goat meat after cooking [33] and was accompanied by a remarkable increase in the IMP content in the chicken broth. [7] Rotola-Pukkila et al [11] have reported that IMP in pork meat remained constant after cooking at 80°C for 120 min.…”
Section: Changes In Faa Content With Different Stewing Timessupporting
confidence: 83%
“…[2,10,31] The decreases in IMP, GMP, and Hx could result from both their migration from the meat into the broth and the thermal degradation of IMP to inosine during stewing. [32] The decrease in the IMP in the chicken meat during stewing were consistent with results in goat meat after cooking [33] and was accompanied by a remarkable increase in the IMP content in the chicken broth. [7] Rotola-Pukkila et al [11] have reported that IMP in pork meat remained constant after cooking at 80°C for 120 min.…”
Section: Changes In Faa Content With Different Stewing Timessupporting
confidence: 83%
“…China is the second largest chicken consuming country, accounting for 15.10 percent of the total world-wide consumption in 2014 (FAS/ USDA, 2014). As a special species in Asia, meat from yellowfeather broilers has a more distinctive flavor than many other commercial broilers such as Arbor Acres and Cobb500 (Chumngoen & Tan, 2015;Jayasena et al, 2015a, b). For this reason it is favored by consumers, especially in Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…China has become the second most consumptions of chicken (FAS/USDA, ). The yellow‐feathered broilers, accounting for approximate 50% heads of chicken in China, were commonly consumed as a special product named soft‐boiled chicken, which has a distinctive flavor and texture (Gao et al., ; Jayasena, Jung, Alahakoon, et al., ; Jayasena, Jung, Bae, et al., ). Korean researcher demonstrated that yellow‐feathered chickens contained higher levels of inosine 5′‐monophosphate, betaine, and carnitine than white commercial broilers (Jayasena, Jung, Kim, et al., ).…”
Section: Introductionmentioning
confidence: 99%